The Effect of Management of Service Strategies on Quality of Public Satisfaction Survey on Nuclear Emergency Response at RSG-GAS Serpong, TRIGA2000 Bandung and Kartini Yogyakarta Research Reactor - Siswo Hadi Sumantri; Dewi Apriliani; IDK Kerta Widana (International Review of Management and Marketing, 2019)
A study has been carried out to contribute to Indonesia's disaster management system for nuclear emergency preparedness and response. This study is very important to improve nuclear emergency preparedness and responses to local authorities who have the potential risk of a nuclear disaster arising from an emergency nuclear research reactor. The difference in reactor power provides an overview of the different potential hazards. This paper analyzes the nuclear emergency response plan of the Indonesian nuclear research reactor. They are RSG-GAS (30 MWth) in Serpong, TRIGA2000 (2 MWth) reactor in Bandung, and Kartini reactor (100 KWth) in Yogyakarta. A good quality management strategy can contribute to people's satisfaction compared to current international standards. This study concludes that the potential danger of the reactor is in line with the power and characteristics of the reactor. Among the three, RSG-GAS has the highest potential hazard with a potential impact of up to 5 Km, followed by the TRIGA2000 reactor with a potential impact of up to 1 Km, and the least is the Kartini reactor with a potential impact of up to 200 m. The operation concept used in the contingency plan is in line with international standards. This research found that a good service strategy management plan is not equipped with a reference value for every protective action taken will cause community satisfaction will not be of good value. Therefore, reviews and updates are needed to improve the plan. Another challenge found in this study, one of which is the availability of Iodine Thyroid Blocking Agent (KI pills), also needs to be solved so that it is prepared for an effective response. Keywords: Management of Service Strategies, Quality of Public Satisfaction JEL Classifications: L1, Q54 DOI: https://doi.org/10.32479/irmm.8835